Educational Financing Management in State Vocational Schools - Handayani, Kristin; Setiyono, Pupuk; Dewi, Dian Novika; Nurkolis , Nurkolis (Universitas Negeri Semarang, 2024)
The research was conducted to evaluate strategies for fulfilling resources and allocating educational financing at SMK Negeri at Blora Regency with the aim of improving the quality of education. The research method was a mix of quantitative and qualitative descriptive methods with purposive sampling techniques, involving the school principal and treasurer as participants. Data collection was carried out through questionnaires, interviews and inspection of school financial documents. The research results show that the process of preparing a budget plan involves meetings with related parties at the Blora Regency Vocational School, but financial policy decisions are still taken top down by the Central Java Provincial Education Office. Fund expenditures are directed in accordance with technical instructions from the Central Java Provincial Education Office, although there are different problems in each school. Supervision and inspections are carried out by the school principal, vice school principal, and the Central Java Provincial Education Office to ensure the effectiveness and efficiency of the use of funds. The process of preparing the School Revenue and Expenditure Budget Plan (RAPBS) is carried out collaboratively by various parties in the school, and supervision of education financing is carried out strictly. The monitoring system involves observing every income and expenditure of funds with direct approval from the school principal or treasurer. The contributions of this research can provide a basis for refining future policies to improve the quality of education and opportunities for students to develop their potential.